Penggandaan Smadav PRO Tanpa Izin Pencipta Ditinjau Dari Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Latukau, Akmal Asamahdi; Akyuwen, Rory Jeff; Labetubun, Muchtar A H (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The development of science as part of the object protected by copyright. One of the creations that are protected by copyright is software, which in this writing is Smadav antivirus software.Purposes of the Research: This study aims to explain and inform about legal arrangements and legal protection to creators regarding the doubling of the Smadav serial number/key in Law Number 28 of 2014 concerning Copyright.Methods of the Research: This study uses normative legal research methods, and the collection of legal materials is carried out by literature study, then analyzed by qualitative means.Results of the Research: The results show that, duplicating the serial number/key from Smadav Pro, there are several factors that influence a person in doing so, including low law enforcement, low public purchasing power for original software, and the rapid development of information technology. Furthermore, if there has been a violation of the software or in this case the duplicating of the Smadav serial number/key, the creators can take steps, namely through mediation, arbitration, or court processes and the application of complaint offenses for criminal charges.